DNA methylation in promoter region of immune related genes STAT3 and VEGFA and biochemical parameters change in muscle of Japanese flounder under acute hypoxia. (April 2022) - Li, Xiaohui; Liu, Binghua; Yang, Jun; Li, Guangling; Wen, Haishen; Zhang, Meizhao; Li, Jifang; He, Feng
Abstract: Acute hypoxic stress can lead to immune response in fish, but the molecular mechanism of muscle immunity in fish under acute hypoxia are still unclear. In this study, we carried out the effect of signal transducer and activator of transcription3( STAT3 ) and vascular endothelial growth factor A( VEGFA ) on muscle immune responses of Japanese flounder ( Paralichthys olivaceus ) during acute hypoxic stimulation (1.65 ± 0.28mg/L O2 ; 3h, 6h, 12h, 24h) and reoxygenation (7.30 ± 0.40mg/L O2 ; R12h, R24h, R48h). In situ hybridization (ISH) showed that STAT3 and VEGFA RNA were co-located in the skeletal muscle of Japanese flounder. Japanese flounder was seriously affected by hypoxia for 3h and 6h. The expression of STAT3 and VEGFA increased significantly. The methylation levels of STAT3 5′UTR region and VEGFA promoter region were significantly lower than those in normoxia group, which was negatively correlated with the expression levels of STAT3 and VEGFA . The enzyme activities (LDH, ALT, AST, ALP) changed significantly. In addition, enzyme-linked immunosorbent assay (ELISA) detected a positive correlation between serum VEGFA concentration and muscle VEGFA mRNA. The current study have shown that Japanese flounder responded to acute hypoxic stress at multiple metabolic levels by changing DNA methylation status and activating transcription factors such as HIF-1α, Nrf2 and STAT3 . It is significant for the scientific development of aquaculture through analyzing the effects of hypoxia on biological immunity. Highlight: Hypoxia activation of STAT3 induced VEGFA in Japanese flounder. Hypoxia significantly increased DNA methylation levels of STAT3 5′UTR and VEGFA promoter. STAT3 and VEGFA RNA were co-located by ISH. Hypoxia induced VEGFA immune responses in Japanese flounder at multiple metabolic levels.